Liver inflammation abrogates immunological tolerance induced by Kupffer cells. Issue 1 (22nd April 2015) - Heymann, Felix; Peusquens, Julia; Ludwig‐Portugall, Isis; Kohlhepp, Marlene; Ergen, Can; Niemietz, Patricia; Martin, Christian; van Rooijen, Nico; Ochando, Jordi C.; Randolph, Gwendalyn J.; Luedde, Tom; Ginhoux, Florent; et al.
<x xml:space="preserve">Abstract</x> The liver is essential for inducing immunological tolerance toward harmless antigens to maintain immune system homeostasis. However, the precise cellular mechanisms of tolerance induction against particle‐bound antigens, the role of the local hepatic microenvironment, and implications for therapeutic targets in immune‐mediated diseases are currently unclear. In order to elucidate cellular mechanisms of tolerance induction in healthy and injured liver, we developed a novel in vivo system combining the systemic delivery of low‐dose peptide antigens coupled to inert particles, immunological readouts, and sophisticated intravital multiphoton microscopy‐based imaging of liver in mice. We show that liver resident macrophages, Kupffer cells (KCs), but not hepatic monocyte‐derived macrophages or dendritic cells (DCs), are the central cellular scavenger for circulating particle‐associated antigens in homeostasis. KC‐associated antigen presentation induces CD4 T‐cell arrest, expansion of naturally occurring Foxp3+CD25+ interleukin‐10‐producing antigen‐specific regulatory T cells (Tregs) and tolerogenic immunity. Particle‐associated tolerance induction in the liver protected mice from kidney inflammation in T‐cell‐mediated glomerulonephritis, indicating therapeutic potential of targeting KC for immune‐mediated extrahepatic disorders. Liver inflammation in two independent experimental models of chronic liver injury and fibrosis abrogated tolerance induction and led to an immunogenic reprogramming of antigen‐specific CD4 T cells. In injured liver, infiltrating monocyte‐derived macrophages largely augment the hepatic phagocyte compartment, resulting in antigen redistribution between myeloid cell populations and, simultaneously, KCs lose signature markers of their tolerogenic phenotype. Conclusions: Hepatic induction of tissue‐protective immunological tolerance against particulate antigens is dependent on KCs as well as on a noninflamed liver microenvironment, thereby providing mechanistic explanations for the clinical observation of immune dysfunction and tolerance break in patients with advanced liver diseases. (Hepatology 2015;62:279‐291)